Aggregated alpha-synuclein mediates dopaminergic neurotoxicity in vivo. - Periquet, M; Fulga, T; Myllykangas, L; Schlossmacher, MG; Feany, M (2007)
Mutations in the synaptic protein alpha-synuclein cause rare genetic forms of Parkinson's disease. Alpha-synuclein is thought to play a critical role in more common sporadic cases of Parkinson's disease as well because the protein aggregates in the hallmark intraneuronal inclusions of the disorder, Lewy bodies. To test the role of protein aggregation in the pathogenesis of Parkinson's disease, we expressed a form of alpha-synuclein with a deletion of amino acids 71-82 that is unable to aggregate in vitro in a transgenic Drosophila model of the disorder. We found no evidence of large aggregates or oligomeric species of alpha-synuclein in these animals and no loss of tyrosine hydroxylase-positive neurons. We also expressed a truncated form of alpha-synuclein that has enhanced ability to aggregate in vitro. This truncated form of alpha-synuclein showed increased aggregation into large inclusions bodies, increased accumulation of high molecular weight alpha-synuclein species, and demonstrated enhanced neurotoxicity in vivo. Our findings thus support a critical role for aggregation of alpha-synuclein in mediating toxicity to dopaminergic neurons in vivo, although the precise role each aggregated form of alpha-synuclein plays in neurotoxicity remains to be determined.